2021
DOI: 10.3390/nu13072163
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Association between Fat Mass Distribution and Bone Mass in Chinese Male Adolescents at Different Stages of Puberty

Abstract: Background: Bone mineral acquisition during adolescence is crucial for maximizing peak bone mass. Fat mass (FM) and bone mass are closely related. This study investigated the association of FM distribution with bone mass in Chinese male adolescents. Method: A total of 693 male adolescents aged 10–18 years were recruited from a secondary school in Jiangmen, China. Their bone mass and body composition were measured by quantitative ultrasound and bioelectrical impedance analysis, respectively. The associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…As adipogenesis and osteogenesis involve dynamic processes related to multiple factors (30), it is challenging to predict the ultimate impact of adipose tissue on bone. The ndings of this study indicate that adipose tissue is detrimental to bone health, which is consistent with those of previous studies (31)(32)(33)(34). Maurin et al (35)found that adipose tissue could inhibit the proliferation of human osteoblasts in vitro utilizing the co-culture paradigm.…”
Section: Discussionsupporting
confidence: 92%
“…As adipogenesis and osteogenesis involve dynamic processes related to multiple factors (30), it is challenging to predict the ultimate impact of adipose tissue on bone. The ndings of this study indicate that adipose tissue is detrimental to bone health, which is consistent with those of previous studies (31)(32)(33)(34). Maurin et al (35)found that adipose tissue could inhibit the proliferation of human osteoblasts in vitro utilizing the co-culture paradigm.…”
Section: Discussionsupporting
confidence: 92%
“…Sex hormone concentration grows in mid-childhood [50]. Puberty, or sex hormone concentration, is a variable that has been suggested to have a significant impact on the relationship between body composition and bone mass [28,51]. In this study, the subgroup analysis showed that the pooled correlation coefficients of LM with total body BMD were higher in adolescents than in children.…”
Section: Discussionmentioning
confidence: 60%
“…However, some of the included studies only had data for total body bone measurements that included the head. Third, it is known that age and puberty stage play an important role in bone development [51]. Due to the lack of specific data, this study could not examine the effects of age or puberty status on the relationships between body composition and BMD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The anthropometric characteristics of participants including age, sex, and BMI were collected. BMI is defined as a participant’s weight in kilograms divided by the square of the height in meters in adults (kg/m 2 ) ( 25 ). Following the WHO BMI norms, the participants were divided into two groups of normal BMI (18.5<BMI<24.9 kg/m 2 ) and excess BMI (overweight/obesity, BMI≥ 25 kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%